Dystocia Due to Poll Presentation in Crossbred Primipara Black Bengal Doe - Subhalagna Dey, Kalpita; Behera, Himanshu; Sri Naga Anirudh, Juturu; Patra, Abhijit; Shekhar Biswal, Shuvranshu (The Indian Journal of Animal Reproduction, 2025)
The presented case of dystocia in crossbred primipara Black Bengal doe with fetus poll presentation (anterior longitudinal presentation, dorso sacral position, flexed fore limbs) was rectified by manual manipulation using small eye hook as obstetrical tool. On per-vaginal examination, cervix was found to be dilated and top of the head (poll region) of fetus was felt which waslater confirmed by diagnostic imaging (X-ray). A dead foetus was delivered by traction through eye hook along with the fetal membrane. The doe was administered with antibiotics, pain killer, Vitamin B complex, calcium and other fluid therapy, ecbolics and the doe recovered eventually.